THE ROLE OF THE MEDAN CITY ELEMENTARY EDUCATION COUNCIL IN DEVELOPING THE QUALITY OF EDUCATION IN THE EDUCATIONAL INSTITUTIONS OF SMP MUHAMMADIYAH 1 MEDAN - Nadlrah Naimi; Uswah Hasanah (Proceeding International Seminar of Islamic Studies, 2022)
. The purpose of this study was to describe the role of the Medan City Elementary Education Council in developing the quality of education at SMP Muhammadiyah 1 Medan. SMP Muhammadiyah 1 Medan is a formal educational institution in Medan City which is highly developed in terms of quality. This is indicated by the categorization of this educational institution as one of the leading schools and the many achievements achieved both formal and non-formal. The Educational Education Council from the central level to the branch level, namely as the organizer of business charities, programs, and activities in the field of Primary and Secondary Education in accordance with the policies of the Association. The Dikdasmen Council organizes, guides and supervises the development of education held in every Muhammadiyah school, including improving the quality of education. The efforts made by the Educational Education Council are to establish cooperative relationships with school principals. This research is a qualitative descriptive study. The results of this study indicate that the role of the Medan City Education Council has been carried out optimally. This is marked by a positive impact on the learning process and increased stimulation for students to perform both in formal and non-formal channels.Keywords : Dikdasmen, Education Quality Development, Educational Institutions